Outbreak Prevention of Dengue Hemorrhagic Fever in the Work Area of the Baqa Health Center, Samarinda City - Sukma Dewi; Sri Sunarti; Yennike Fitriana; Nida Amalia; Weldy Andy Arif; Sunia Eka Puspita; Nur Afifah Agsyam; Maria Indri Novita Sari (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2023)
Dengue hemorrhagic fever is one of the endemic diseases in East Kalimantan, which is caused by the dengue virus through the bites of the Aedes aegypti and Aedes albopictus mosquitoes that bite humans. Samarinda City is one of the areas that has experienced an increase in DHF cases, especially in the working area of the Baqa Health Center. This community service activity aims to carry out epidemiological investigations to prevent and limit DHF transmission in the working area of the Baqa Health Center. Activities carried out during the DHF epidemiological investigation include observing the surroundings of the house, examining larvae at the houses of DHF sufferers or other suspects as well as the environment around the house, visits to RTs related to anticipating the spread of DHF cases by providing leaflets and abates and providing larva observer books at each house. The results of the activity show that the response to epidemiological investigations is effective in increasing public knowledge and awareness of DHF transmission. The proactive attitude of the community to report DHF cases also needs to be done so that there are no delays in intervening DHF cases.